Utilization Of Technology In Operational Debt Data Processing At PT. Pegadaian Regional Office XII Surabaya: Pemanfaaatan Teknologi Dalam Pengolahan Data Hutang Operasional Pada Perusahaan PT. Pegadaian Kantor Wilayah XII Surabaya - Annisa Setia Anggraini; Yuniningsih (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Finance is the most important aspect of a business activity, both individually and in a company. One of the applied sciences in the field of finance is accounting. Accounting can be applied to the bookkeeping process which is part of the company's financial report data. PT. Pegadaian Regional Office XII Surabaya has currently integrated software and hardware technology to complete various financial tasks. The technology is in the form of hardware such as computers/laptops, as well as software in the form of the internet, Microsoft Excel, STRIVE (trading online application), and SAP (Systems, Applications, and Products in Data Processing). In connection with the implementation of the MBKM internship, students were given the opportunity by PT. Pegadaian to participate in the Finance Department by processing operational debt data to admin costs. The results of this activity have a fairly good impact on students' insights regarding the use of technology in direct work in the field, and PT. Pegadaian obtains adequate financial report data when needed on the periodic audit schedule.